Epistemological and ontological dualities as a challenge for a holistic modernity - Hermes Andreas Kick (Proceedings (European Academy of Sciences and Arts))
This paper explores the philosophical, scientific, and artistic dimensions of home, alienation, and the slow return home as a framework for understanding the crises of modern knowledge and existence. It critiques the dominance of reductionist objectivism in science and the fragmentation of meaning in contemporary culture, arguing that both subjective and relational perspectives have been undervalued. Drawing on thinkers such as Karl Jaspers, Martin Heidegger, and Wilhelm Dilthey, the study examines how unresolved epistemological and ontological dualities—such as subjectivism versus objectivism and materialism versus idealism—have shaped intellectual and cultural developments since the Enlightenment. The concept of the border situation, introduced by Jaspers, is central to this analysis, describing moments of existential rupture that force individuals and societies to confront fundamental contradictions. The slow return home is presented not as a simple restoration of tradition but as a dynamic process of integration, where insights gained through alienation enable a deeper, reconstructed sense of belonging. By maintaining a dialectical balance between objectivity and subjectivity, science and art, rationality and intuition, this paper advocates for an approach to knowledge that transcends ideological rigidity and fosters existential illumination.